Posttraumatic invasion of monocytes across the blood–cerebrospinal fluid barrier - Szmydynger-Chodobska, Joanna (Nature Publishing Group, 2012)
The invasion of inflammatory cells occurring after ischemic or traumatic brain injury (TBI) has a detrimental effect on neuronal survival and functional recovery after injury. We have recently demonstrated that not only the blood–brain barrier, but also the blood–cerebrospinal fluid (CSF) barrier (BCSFB), has a role in posttraumatic recruitment of neutrophils. Here, we show that TBI results in a rapid increase in synthesis and release into the CSF of a major chemoattractant for monocytes, CCL2, by the choroid plexus epithelium, a site of the BCSFB. Using an in vitro model of the BCSFB, we also show that CCL2 is released across the apical and basolateral membranes of the choroidal epithelium, a pattern of chemokine secretion that promotes leukocyte migration across epithelial barriers. Immunohistochemical and electron microscopic analyses of choroidal tissue provide evidence for the movement of monocytes, sometimes in tandem with neutrophils, along the paracellular pathways between adjacent epithelial cells. These data further support the pathophysiological role of BCSFB in promoting the recruitment of inflammatory cells to the injured brain.